Sociodemographic and histopathological characteristics of patients with gastric cancer in a high-risk population in Colombia (2020)
Objective: To describe the sociodemographic and histopathological characteristics of patients diagnosed with gastric adenocarcinoma at the Clínica Oncológica Aurora between 2014 and 2017 in the city of Pasto, Colombia. Methodology: A descriptive study was carried out in a cohort of 54 patients diagnosed with gastric cancer who underwent gastrectomy between 2014 and 2017. Sociodemographic information was taken from the medical records of the patients. The Sydney system and Lauren classification were used to determine histopathological characteristics. Results: Most tumors were found in men older than 50 years (with a male:female ratio of 2.6:1). The predominant location was the antropyloric region. The most frequent tumor histotype was intestinal (80 %). The prevalence of Helicobacter pylori in patients was 24.07 % and it was most commonly found in the intestinal histotype. Intestinal metaplasia was the most prevalent premalignant lesion in all tumor histotypes. Conclusions: The present study found that the age of 50 and the male sex are conditions associated with gastric cancer. This finding has already been demonstrated in previous studies. Progress in improving public health conditions, controlling H. pylori infection, and early screening of premalignant lesions is imperative, as they are determining factors of carcinogenesis in patients with non-cardia carcinomas and intestinal histotypes located in the anthrocorporal region. Although no significant differences were found among tumor histotypes, intestinal ade